Effects of environmental carcinogen benzo(a)pyrene on canine adipose-derived mesenchymal stem cells. (December 2015) - Rathore, Kusum; Cekanova, Maria
ABSTRACT: Dogs and their owners share the same environment and are subjected to similar environmental risk factors for developing breast cancer. Adipose tissue-derived mesenchymal stem cells (ADMSCs) may affect development and progression of breast cancer. In this study, we evaluated the effects of environmental carcinogen benzo(a)pyrene (BaP) on proliferation and differentiation of ADMSCs isolated from dogs. We characterized eight canine ADMSC lines and studied the effects of BaP on cell proliferation and differentiation. BaP did not inhibit cell proliferation of ADMSCs; however, BaP significantly inhibited differentiation potential of ADMSCs into adipocytes. BaP down-regulated AhR protein levels; however, increased its translocation from the cytoplasm to nucleus and suppressed PPARγ expression during adipogenesis. BaP increased the expression of AhR signaling pathway protein, cytochrome P450 (CYP1A1) in ADMSCs. Our data suggest that canine ADMSCs are susceptible to the environmental carcinogen BaP through AhR and PPARγ signaling pathways and may contribute to canine mammary carcinogenesis. Highlights: Benzo(a)pyrene inhibited differentiation of canine adipose-derived mesenchymal stem cells into adipocytes. Benzo(a)pyrene inhibited AhR and PPARγ signaling pathways. Benzo(a)pyrene increased translocation of AhR from cytoplasm into nucleus during adipogenesis. Canine adipose-derived mesenchymal stem cells are susceptible to the environmental carcinogen benzo(a)pyrene.